Can Poor Hydration Amongst Older Hospitalized People be Identified by Single Point Total Body Water Assessment? – A Pilot Study - Angela Vivanti (Journal of Aging Research And Healthcare, 2017)
Dehydration in acute care is associated with increased morbidity and mortality. However, no standard approach to hydration assessment exists in clinical settings. The pilot study aimed to explore total body water content as means for immediately assessing hydration status in clinical settings. People aged 60 years or more, voluntarily admitted to a tertiary teaching hospital’s Geriatric and Rehabilitation Unit were eligible for participation. Total body water assessment by tracer dilution was compared with standard clinical assessment of hydration status. The study participants (78.6±8.5 years, 6/14, 43% male) clinically assessed with poor hydration (3/14) had a higher percentage of body weight as water (59.0±2.3 vs 50.6±6.4%), and lower mean weight (54.1±12.9 vs 77.5±24.1 kg) and lower body mass index (20.0±3.7 vs 30.2±6.5 kg/m2) than the well-hydrated (11/14). Weight (n=14) and body mass index (n=11) explained a substantial proportion of variation in total litres of body weight as water (r=0.92, R2=0.85; r=0.80, R2= 0.64) and percentage of body weight at water (r=0.6, R2= 0.36; r=0.72, R2= 0.52) respectively. This pilot study revealed higher percentages of body weight as water amongst those clinically assessed with poorer hydration. Future regression analysis of total body water and hydration needs to adjust for the potential confounding effect of weight and body mass index. Implications for practice from this preliminary study indicate that findings did not support single point measurements of either total body water or percentage of body weight as water as potentially simple methods for clinically assessing hydration status amongst older hospitalised people.
Keywords: Dehydration